An Exploratory Survey of Incorporation of Gender- and Sex-related Differences in the PharmD Curricula - Kelsea Caruso; Brooke Griffin; Kathleen Vest; Spencer Harpe (University of Minnesota Libraries Publishing, 2018)
Introduction: Clinical presentation and treatment in many disease states vary due to sex- and gender-differences. Sex-related pharmacokinetic differences are particularly important for pharmacists. The Accreditation Council for Pharmacy Education (ACPE) currently has no standard for the inclusion of gender- and sex-related differences in the didactic PharmD curriculum, but encourages advanced pharmacy practice experiences (APPEs) to include diverse populations related to gender. The purpose of this survey is to explore faculty incorporation of gender and sex differences within the PharmD didactic curriculum in preparation for a nation-wide survey.  Methods: A survey was created to determine how many clinical topics incorporated gender- and sex-related differences and to what extent this information was discussed in the classroom. The survey link was emailed to pharmacotherapeutics and pharmacokinetics faculty at Midwestern University Chicago College of Pharmacy, University of Illinois at Chicago, Roosevelt University, Rosalind Franklin University, and Chicago State University. Chi square analyses were performed to examine relationships across participant responses.  Results: A total of 56 faculty members participated in the survey, resulting in a 20% response rate. Of these, 30 (54.5%) faculty indicated that they discussed gender- and sex-related differences in the subject area in which they teach. Approximately 33% of respondents found gender- and sex-related differences very clinically important. Gender- and sex- related differences were taught in a variety of subject areas, including cardiology, diabetes, and chronic obstructive pulmonary disease (COPD). Conclusion: With no current standard, faculty members independently choose to include gender- and sex-related differences in their lecture topics and the extent of the discussion. Faculty should be aware of this lack of standardization and that they are independently responsible for including gender- and sex-related differences in their particular topics.  Because the surveyed faculty find gender- and sex-related differences clinically important and literature suggests differences in medications depending on gender and sex, further research is planned to provide insight on a national level. Treatment of Human Subjects: IRB exemption granted   Type: Original Research